Islamic tourism: beyond than just Halal food and a place for prayer - Mahamod, Lukman Hakim; Wan Yahya, Wan Nur Amirah; Wan Shamsuddin, Wan Norshafiqah; Othman, Rashidi; Hashim, Khairusy Syakirin Has-Yun; Ibrahim, Mansor (American Scientific Publishers, 2015)
This paper is concerned with the Islamic tourism product that is shariah compliant accommodations. The overviews of Islamic tourism can be identified based on the literature review available. In Malaysia context, Islamic tourism can be defined as any activities, events and experience undertaken in a state of travel that is in accordance with Islamic teaching. This concept is widely discussed among the researchers as a result of the increasing number of Muslim travellers around the world recently. However, the Islamic tourism concept is always mistakenly understood where it is actually beyond than just halal food and availability of prayer places. The present studies focused on the operation stage, but the design and construction stage of shariah compliant hotel are remained undiscovered. Therefore, this paper will focus on the linkage of shariah compliant hospitality with construction industry during the design stage.